Designing of Hairpin-Line Band Pass filters for DCS, UMTS and LTE-Systems - Muhammad Sayidi; Mudrik Alaydrus (InComTech : Jurnal Telekomunikasi dan Komputer, 2015)
Bandpass filters are essential components in any wireless systems. They are designed for selecting desired signal from other signals. Especially in crowded frequency spectrums, accurate filter characteristics are required to guarantee the performance of the overall systems. DCS, UMTS and LTE systems are the actual communication systems used by hundred million users. Bandpass filters designed here is based on hairpin line structures and implemented in microstrip technology. The filters are five order Chebychev’s bandpass filters. The center frequency of each system determines the total length of the U-form hairpin structure. The design starts with exploiting the coupling between the resonators. The coupling between two adjacent resonators is determined by the fractional bandwidth of the system and the element value derived from the Chebychev’s approximation. The value of the coupling factor leads to the distance between two adjacent resonators. The simulation results conform to the specifications given in the standards. In general, the measurements verify the simulation. We see worse reflection factors and more insertion loss eventually due to bad soldering of the connectors to the filters. The shifting and width of the pass regions are also observed, which are probably due to the finite accuracy in prototyping the filters.